The efficacy of phenytoin dressing in healing of diabetic ulcer: a randomized control study - Gunasekaran, Vijay; Subbaraj, Saravanakumar; Aroul, Tirou (International Surgery Journal, 2017)
Background: Diabetic foot infection constitutes up to 10 percent of diabetes-related hospital admissions and the prevalence of diabetes is 2.4% in rural and 12-17% in urban settings. The quest for better wound healing agents for diabetic ulcers is perhaps one of the oldest challenges for medical practice. One such agent that has been tried in wound healing is phenytoin. A common side effect of phenytoin (diphenylhydantoin) treatment for epilepsy is gingival hyperplasia. This stimulatory effect of phenytoin on connective tissue suggested a possibility for its use in wound healing. Methods: 60 patients with diabetic foot ulcer admitted in General Surgery at Mahatma Gandhi Medical College and Research Institute, Puducherry, India were randomly assigned into two groups, the study group consisting of 30 patients who were treated with phenytoin dressing and 30 patients into control group who were treated with conventional saline dressing. Both groups underwent initial debridement and were started on parenteral antibiotics according to wound swab culture and sensitivity. Study group were treated with phenytoin dressing and the wound was assessed based on the rate of ulcer size reduction, the rate of granulation tissue, duration of hospital stays and antibacterial property of phenytoin. Patients were assessed weekly up to 21 days. Results: The rate of granulation tissue in phenytoin group was 90.36% which was statistically significant (p = 0.0011) as compared to control group which was 82.03%. Wound swab cultures repeated on day 21 revealed that there was 50% negative culture in phenytoin group when compared to control group of 24% which also was statistically significant. The mean hospital stay for the patient in phenytoin group was 29.2 days and in control group, it was 26.1 days. It was observed that surface area reduction in phenytoin group was 41.25cm2 to 18.38cm2 and in control group was 40.28cm2 to 20.23cm2 by the end of 21 days, but this was not statistically significant. Conclusions: Phenytoin dressing is effective in increasing the rate of granulation tissue by virtue of its action on stimulating fibroblast proliferation and decreasing collagenase activity. It not only hastens granulation tissue but also decreases bacterial load as compared to conventional dressing by virtue of its intrinsic antibacterial activity and indirectly through their effects on anti-inflammatory cells and neovascularization. Phenytoin prepares the foot ulcer for early grafting thereby improving the overall outcome.